Microstructures and mechanical properties of CoCrFeNiMn high-entropy alloy coatings by detonation spraying. (May 2021) - Liao, Wei-Bing; Wu, Zhong-Xuan; Lu, Wenjun; He, Minjun; Wang, Ting; Guo, Zongxiao; Huang, Jianjun
Abstract: CoCrFeNiMn high-entropy alloy (HEA) coatings were deposited on 316L stainless steel substrate by detonation spraying technique. The HEA coatings had a dense microstructure and contained a small amount of flocculent metal oxides, showing a main face-centered-cubic (FCC) solid solution structural matrix with amounts of nano-multi-component metal oxides. It was found that the microhardness of CoCrFeNiMn HEA coating by detonation spraying was much higher than that prepared by direct casting or spark plasma sintering due to the multi-component metal oxides reinforcement and fine grain strengthening effect. Furthermore, the HEA coating by detonation spraying exhibited excellent abrasive wear resistance and bond strength. The analysis of coating failure verified that the failure of the HEA coating was mainly due to lamellar structures peeling off. The CoCrFeNiMn HEA coatings with outstanding mechanical properties could be promising for application in future as structural materials. Highlights: CoCrFeNiMn high entropy alloy coatings were prepared by denotation spraying. A small amount of flocculent oxide was formed in the high entropy coating. Microhardness of CoCrFeNiMn coating by detonation spraying was ~471 HV The coating exhibited excellent abrasive wear resistance and bonding strength.